Pembuatan Biofuel dari Limbah Cair PMKS dengan Katalis MoCo-HZ - Tyas Sri Muryati; Agus Sundaryono; Dewi Handayani (ALOTROP, 2018)
This research aims to convert vegetable oils contained in Palm Oil Mill waste (PMKS) into biofuels through the cracking process with MoCo-HZ catalyst . PMKS Liquid waste will be prepared with a process of a filtering, degumming, bleaching, warming, and free Fatty Acids determination.  The results obtained are then converted into biofuel with catalytic cracking with use of MoCo-HZ catalyst . Then the cracking products will to test for specified physical characteristics of biofuel eq : acid number , density, viscosity, pour point and cloud point. . The research results showed that the MoCo-HZ catalyst is able to convert vegetable oils contained in the PMKS liquid waste will be cracked into biofuel. Conversion yield obtained is amounting to 48.19%. The physical characteristics of the test results against biofuels produced from the cracking process has not met the standard of comparison from gasoline and kerosene. This is shown by the still high number of biofuel produced acids amounting to 1.72 mg KOH/gr. higher than the numbers of  sour gasoline (0.748 mg KOH/gr) and Kerosene (0.935 mg KOH/gr). The result of the test of density, viscosity, pour point and cloud point against biofuels produced from the cracking process have meet standard compared to gasoline and kerosene respectively 0.807 gr/cm for density, 1.056 cSt viscosity for viscosity , and 0 º C and 1.33 each º C to the freezing point and the cloud point..